The Rise of Digital Health: A Bibliometric Review of Social Media and Online Platforms for STI Education in Adolescents - Henky Yoga Prasetya; Sri Ratna Rahayu; Widya Hary Cahyati (Journal of Foundational Learning and Child Development, 2026)
Purpose of the study: Sexually Transmitted Infections (STIs) continue to increase, especially among adolescents. Minimal sexual education and risky behaviors are the main factors in STIs. In the digital era, social media has the potential to be an effective means of STI education for adolescents. However, scientific studies related to this matter are still limited. This study aims to map the current research landscape regarding the use of social media and online platforms for STI education among adolescents. Materials and methods: This study uses a bibliometric approach. Literature searches were conducted in the Scopus database using keywords such as "social media", "online platforms", "IMS/IST education", "adolescents", and "health" for period 2014-2024. Results: An analysis of 428 documents that met the inclusion criteria showed a very rapid increase in publications related to this topic, with an annual growth rate of 78.5%. The results of the network visualization identified four main clusters, namely: (1) the effectiveness of digital health campaigns; (2) the role of social media platforms such as Instagram, TikTok, and YouTube in the dissemination of information; (3) factors that affect the behavior of receiving health information online; and (4) the development of mobile app-based health interventions (mHealth). Conclusions: Digital health for adolescent STI education is growing rapidly and multidimensional. The initial surge in publications reflects a response to the global crisis, followed by a deepening of approaches and topics. Bibliometric visualization emphasizes the importance of interdisciplinary and innovative approaches in dealing with adolescent health challenges in the digital age